IMPACT OF BRAND, PACKAGING AND WARRANTY ON PURCHASE DECISION (Case Study of Pantene Shampoo Consumers in Sidoarjo) - Mahjudin Mahjudin; David S; I Gede Wiyasa (Journal of Managerial Sciences and Studies, 2024)
The success of a company in carrying out its activities is largely determined by its ability to market its products. This shows that marketing is the spearhead for a company in achieving its goals. In order to win the competition in the current era of free trade, companies are required to implement the right strategy so that the marketing program implemented is truly on target so that the marketing of the company's products will be successful. Competition between companies that provide products with the best attributes for consumers, so that good product attributes can make a major contribution to consumer satisfaction, market share, and profitability both in price, shape or product design. Therefore, the company must be able to position its products according to the needs and desires of consumers appropriately, so that consumers can distinguish the products offered and the products stick in the minds of consumers. The data used in this study are primary data, namely data obtained through distributing questionnaires to consumers who consume Pantene Shampoo in Sidoarjo and secondary data, namely data obtained from companies that are used as research objects. The analysis technique used in this study is using multiple linear regression analysis. While the statistical test uses the F test and t test. The results of the study obtained the F count value (111.9358)> F table (2.70) which means that Brand, Packaging, and Guarantee simultaneously influence Purchasing Decisions. The brand variable has a significant effect on purchasing decisions with a t count value of 6.5062> from t table 1.9850. The packaging variable has a significant effect on purchasing decisions with a t count value of 3.9372> from t table 1.9850. The guarantee variable has a significant effect on purchasing decisions with a calculated t value of 4.9329 > from the t table of 1.9850.